The Caribbean: culture of resistance, spirit of hope - Bolioli, Oscar L. (Friendship Press, 1993)
The Caribbean: culture of resistance, spirit of hope despites centuries of exploitation and oppression, the people of the Caribbean have an indomitable spirit, expressed in the very diversity of their culture, politics and religion